Caracterização em acessos de melão do Banco Ativo de Germoplasma de cucurbitáceas para o Nordeste brasileiro - Amorim, Clisneide Coelho de (2016)
The melon (Cucumis melo L.) production is growing steadily in the last years and it is demanded for the internal as well as the external markets. The melon produced belongs to the botanical group inodorus, yellow type, although the cultivars used present susceptibility to biotic stresses and, therefore, there is a need to search new germplasm in order to give support to melon breeding programs. On the other hand, there are melons cultivated by small farmers in the traditional agriculture of Northeast Brazil and a sample of these melons is stored in the Active Germplasm Bank of Cucurbits for the Northeast Brazil, located in the Semiarid Embrapa, at Petrolina-PE. Thus, the present study aimed at to estimate the genetic variability within and among melon accessions using morphological and molecular markers in order to identify the melon subspecies and their respective botanical groups. In the morphological characterization the parental e S1 generations were used recording quantitative and qualitative descriptors and some accessions were partitioned in subacessios. In the molecular characterization 28 ISSR primers were used. Using the morphological data is was possible to identify the subspecies agrestis with the botanical groupsmakwua and momordica and the subespecies melo with the botanical group cantalupensis. The UPGMA clusters showed great genetic diversity within and among the accessions and subaccessions. There was a reasonable agreement between the clusters based on morphological and molecular data, although the molecular data were more precise in the separation of the clusters. However, there is indication of introgression of traits of different subspecies and their botanical groups in the melon cultivated in the traditional agriculture of Northeast Brazil.